Immigration Shocks and Shifting Social Group Boundaries - Zohal Hessami; Sebastian Schirner (Institute of Labor Economics (IZA), 2024)
We study whether the arrival of a new immigrant wave changes natives' acceptance of former immigrants and their descendants. We exploit the 2015 European refugee crisis and the context of German open-list local council elections where voting for immigrant-origin candidates represents a consequential revealed preference. We combine hand-collected candidate-level election data with administrative asylum seeker data. Continuous difference-in-differences estimations (based on municipal %∆ in asylum seekers) reveal that immigrant-origin candidates receive more votes the more asylum seekers arrived locally. This shift in social group boundaries is driven by candidates with a Southern/Eastern European origin being culturally similar to Germans.
Keywords: D72; F22; J11; J15; N34; 330; immigration; immigrant-origin candidates; local elections; social acceptance; cultural similarity